1992
DOI: 10.1093/jac/30.suppl_a.107
|View full text |Cite
|
Sign up to set email alerts
|

Cellular uptake and intracellular bactericidal activity of RP 59500 in murine macrophages

Abstract: RP 59500, a new antibacterial agent, is a combination of two compounds, RP 54476 and RP 57669. The uptake of radiolabelled RP 59500, i.e. a mixture containing [14C]-RP 54476 plus RP 57669 or [14C]-RP 57669 plus RP 54476, by J 774 murine macrophages was evaluated by a velocity gradient centrifugation technique. After 120 min, the ratios of cellular to extracellular concentration for RP 54476 and RP 57669 were 34 and 50, respectively. The highest intracellular accumulation of RP 59500 was observed at pH 7-7.5. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…It is more tempting to speculate that this may result from the cellular accumulation of quinupristin and dalfopristin. Previous studies using radiolabelled compounds found accumulation levels of 34 and 50 for quinupristin and dalfopristin, respectively, 24 a level globally similar to that of macrolides and ketolides in this set-up. 28,51 Their subcellular localization has not been established, but their weak basic character, and the impairment of accumulation seen in cells exposed to acidic pH, 51 strongly suggest a proton-trapping mechanism in acidic membrane-bounded vacuoles, as demonstrated for macrolides 53 and many other weak organic bases.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…It is more tempting to speculate that this may result from the cellular accumulation of quinupristin and dalfopristin. Previous studies using radiolabelled compounds found accumulation levels of 34 and 50 for quinupristin and dalfopristin, respectively, 24 a level globally similar to that of macrolides and ketolides in this set-up. 28,51 Their subcellular localization has not been established, but their weak basic character, and the impairment of accumulation seen in cells exposed to acidic pH, 51 strongly suggest a proton-trapping mechanism in acidic membrane-bounded vacuoles, as demonstrated for macrolides 53 and many other weak organic bases.…”
Section: Discussionsupporting
confidence: 68%
“…12,21,22 As this phenotype is often co-associated with those resistant to methicillin (MRSA) and with reduced susceptibility to vancomycin (VISA), quinupristin/dalfopristin now appears to be one of those last resource drugs for the clinician facing staphylococcal infections with such multiresistant isolates. 23 Both components of quinupristin/dalfopristin have been shown to accumulate to high levels inside phagocytic cells, 24 and quinupristin/dalfopristin has proven active in models of intracellular infections caused by S. aureus, 24,25 including VISA strains 26 and small colony variants. 27 In the present study, we have compared the extracellular and intracellular activities of quinupristin/dalfopristin against a panel of S. aureus (reference strains and clinical isolates) displaying specific mechanisms of resistance to streptogramins A or B.…”
Section: Introductionmentioning
confidence: 99%
“…A number of models have therefore been developed to assess the potential of other antibiotics, such as rifampin, clindamycin, or glycopeptides (2,12,34), against intracellular S. aureus. Antibiotics with known cellular accumulation such as macrolides (23,38,48,60), synergistins (17), or fluoroquinolones (3,4,10,46,50) have also been studied. While providing useful information, these models have so far been used to examine only short periods of incubation and have not fully taken into account (i) the slow rate of intracellular accumulation of some antibiotics (see reference 57 for comments) and (ii) the reduced growth rate of intracellular S. aureus in comparison with that of bacteria in broth or other more favorable media (29).…”
mentioning
confidence: 99%
“…More potent anti-P. carinii agents may be discovered among other streptogramins and, with the aid of the P. carinii genome project (24), may bring new insights into the mechanism of drug action. There may also be increased understanding of other interesting properties of Q-D, such as its short half-life, long postantibiotic effect, concentration in macrophages, and suppression of cytokine responses (2,3,4,5,6,7,14,20,21). This study was supported by the Medical Research Service, Department of Veterans Affairs, and by Public Service contract AI 75319 and grant RO1 HL64570 from the National Institutes of Health.…”
mentioning
confidence: 99%